The brief overview, antivirus and anti-SARS-CoV-2 activity, quantitative methods, and pharmacokinetics of cepharanthine: a potential small-molecule drug against COVID-19 - Xia, Binbin; Zheng, Li; Li, Yali; Sun, Wenfang; Liu, Yang; Li, Liushui; Pang, Jingyao; Chen, Jing; Li, Jiaxin; Cheng, Hua (Frontiers in Pharmacology, 2023)
To effectively respond to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), an increasing number of researchers are focusing on the antivirus activity of Cepharanthine (CEP), which is a clinically approved drug using for over 70 years. This review aims to provide a brief overview of CEP and summarize its recent findings in quantitative analysis, pharmacokinetics, therapeutic potential and mechanism in anti-virus and anti-SARS-CoV-2 activity. Given its remarkable capacity against SARS-CoV-2 infection in vitro and in vivo, its primary target organ being the lung, its good pharmacokinetic profile, mature and stable manufacturing technique, as well as its advantages of safety, effectiveness, and accessibility, CEP has become a promising drug candidate for treating COVID-19 despite being an old drug.